Risk, crime and gender - Chan, Wendy; Rigakos, George S.; Johnson, Bruce D.; Wesley, Damaris (The British journal of criminology, 2002)
This article offers a feminist critique of risk theorizing for criminology. Current theoretical discussions of risk society' and governmentality are critically appraised with reference to gender, raising questions about the nature of risk for various social groups. Theories of risk taking and risk management in late modernity have assumed a general universality of calculation and effect borne out of instrumental science. Women's negotiation of risk, however, both in terms of risk taking and risk avoidance point to an understanding of risk as inherently gendered and not easily universalized. Moreover, theorizing risk from a gendered perspective highlights its political nature, challenging the idea of risk as a neutral concept and risk assessment as an intended apolitical actuarial practice of late modernity. Instead, we contend that how women experience risk and how we view such experiences are shaped by the politics of gender. Formulations of risk are deeply embedded in gender, race and class politics, and the narrow conception of risk taken in criminological writings has consequently excluded women's experience of crime